The Quest for Innovation: Addressing User Needs and Value Creation - Campos, Hugo (Springer, 2021)
In agricultural and agrifood systems, like in many other economic sectors, the main innovation drivers have traditionally been (1) technological advances and (2) research and development. When innovation fails to address the actual needs of clients and end-users, however, satisfaction gaps are created. The result is that investors receive insufficient returns and end-users receive less than expected value. The consequences of failure can be deeper than just financial, however. Successful innovation in agriculture and agrifood systems is critical to secure affordable, nutritious, and safe food for all people. Rapid innovation is needed to address the serious challenge of climate change and to reduce agriculture’s global environmental footprint. The overarching goal of agricultural innovation should be to deliver high value to end-users and improve their quality of life and well-being. To achieve this goal, organizations must first understand the jobs to be done concept for their end-users. They must take into account user satisfaction gaps and frustrations. Understanding user needs is as important as producing technology to finding innovative solutions. This is true around the globe; in industry and public sectors, and in both developed and developing countries. This chapter explains why investing in innovation is very different from succeeding at it. Ultimately, the examples, ideas, and guidelines in this chapter can be brought to bear on agricultural innovation efforts (and any other economic sector), to make them more productive and worthwhile for end-users and investors/funders. The information herein is meant to increase the likelihood of successful innovation efforts at both profit-seeking firms and nonprofit organizations.